The recent evolution of competition policy in Brazil: an incomplete transition - Mattos, César (Revista do IBRAC, 2025)
This article emphasizes some aspects of the transition in competition policy law and its application in Brazil in the nineties. We use Khemani and Dutz’s (1992) classification about the three Schools of thought in competition policy: Structuralist, Statist and Chicago.